Usage of Fruit-Infused Water for Prevention of Dehydration Due to Endurance Exercise - Ali, Mohammad Arif; Rahayu, Setya; Indardi, Nanang; Anggita, Gustiana Mega; Soraya, Fatona; Rustadi, Tri; Wicaksono, Anggit; Chen, Yu Shiuan; Chang, Yun Zhen (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2018)
This study aimed to extend previous investigation regarding its beneficial effects on changes of blood glucose. This experimental research was conducted from 06:00-12:00. Twenty-four young men (age 19-20 y.o.) were divided into three groups, Fasting-Exercise-Only (FEO), Fasting-Exercise-Water (FEW), and Fasting-Exercise with Fruit-Infused Water (FEF). Subjects underwent fasting for 12 h before the experimental day. The data of body weight (Kg) and macroscopic urine color were collected before and after exercise. Body weight in all experimental groups were decreased by 1% during endurance exercise. There were no differences in decrease of body weight between FEF and FEW groups compared to FEO group (p>.05). The change in urine color was significantly different between pre-exercise and post-exercise data (p<.05). The darkest urine color was observed in FEO group (4.75), followed by FEW group (4.25), while FEF group (3.63) did not reach dehydration level. In conclusion, fruit-infused water is suggested to be drink as a choice for fluid intake during exercise.